Strategi Pemberdayaan Masyarakat dalam Pengembangan Desa Wisata Limbasari, Kabupaten Purbalingga - Ainnuha Nurul Utami; Sungkowo Edy Mulyono (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the community empowerment strategy in the development of Limbasari Tourism Village and identify the supporting and inhibiting factors that influence the process. This study uses a qualitative descriptive approach, with data collection techniques including direct field observation, in-depth interviews with various stakeholders, and documentation of various sources and related activities. The results show that the community empowerment strategy implemented in the development of Limbasari Tourism Village consists of five main stages. The first stage is human resource development through training, education, and capacity building of local communities so that they can play an active role in tourism activities. The second stage is institutional development, which is carried out by strengthening the role of village organizations and forming tourism awareness groups. The third stage includes community investment, both through independent funding and support from external parties. The fourth stage is the development of productive businesses based on local potential, such as handicrafts, village culinary specialties, and tourism services. The final stage is the provision of appropriate information aimed at increasing community access to knowledge and opportunities in the tourism sector. Supporting factors for tourism village development include abundant natural and cultural potential, the active role of village institutions, and support from external parties such as local government, NGOs, and academics. However, several significant inhibiting factors exist, including a lack of understanding of the concept of a tourism village among some residents, uneven community participation, unpredictable weather conditions that impact tourist visits, and inadequate village infrastructure. Therefore, sustained efforts and collaboration from all parties are needed to optimize community empowerment strategies so that the development of Limbasari Tourism Village can be sustainable and provide economic, social, and cultural benefits to the local community.